Combination of organic farming and flower strips in agricultural landscapes – A feasible method to maximise functional diversity of plant traits related to pollination - Katalin Szitár; Balázs Deák; Melinda Halassy; Carolina Steffen; Péter Batáry (Global Ecology and Conservation, 2022)
Agri-environment schemes (AES) are valuable instruments to support pollination in agricultural landscapes. Evaluating AES based on their effects on pollinators has high practical relevance for agricultural production and nature conservation. In our two-year assessment, we studied the effectiveness of two AES (organic farming vs flower strips) on plant traits associated with pollinator attraction (flower size, colour, and ultraviolet pattern) and reward accessibility (flowering duration, and nectar quantity). We selected ten landscapes along a landscape-scale field size gradient in Central Germany. Three types of winter wheat fields (organic, and conventional fields with and without flower strips) were chosen in each landscape. We sampled the vegetation in transects designated in characteristic field parts, i.e. grassy margins, field edges (or flower strips), and field interiors in the growing seasons of 2016 and 2017. We calculated community-weighted means and functional diversity of plant traits and tested the effects of field size, management, and within-field position with linear mixed-effects models. We showed that organic fields and flower strips provided more abundant and functionally more diverse flowers than conventional fields. Flower strips were superior with the highest insect-pollinated plant cover and the highest ratio of plants with flowers showing ultraviolet patterns. Although grassy margins next to flower strips harboured twice as many species as those without flower strips, this positive effect did not emerge in conventional field interiors. Landscape configuration expressed as mean field size did not affect pollination traits in our study. Our results highlighted that both organic farming and flower strips maintained abundant and functionally diverse insect-pollinated flora, and thus they can potentially support larger pollinator communities. However, only organic farming could maintain high functional diversity of pollination-related plant traits in field interiors. Hence flower strips and organic farming in combination might be a good option for sustaining diverse pollinator communities and their services.